Internet service monitoring with mobile agents. - Gunter, M. (IEEE Network : the magazine of global information exchange)
The Internet Engineering Task Force standardizes new IP technologies such as Differentiated Services and IP security that allow Internet service providers to offer new and enhanced network-level services. There is a need for a measurement infrastructure to monitor services, especially for support of end-to-end services across the Internet. The infrastructure should provide a safe way for customers to monitor the enhanced properties of the services they use. Also, providers should be able to use the infrastructure to ensure provider collaboration. We implemented a mobile-agent-based monitoring infrastructure for new and enhanced IP services